I have 2 standard normal, bivariate correlated random variables, $corr \ (X_1, X_2)=\rho$.

I want to generate two independent standard normal random variables from these 2.

I tried to use what I learned from my previous thread: How does the formula for generating correlated random variables work?

I got the following:

$0=cov(\alpha X_1+\beta X_2, X_1)=\alpha\cdot cov(X_1X_2)+\beta\cdot\rho=\alpha+\beta\rho$



But then I can't proceed. Can someone help me with that?

  • 2
    $\begingroup$ So what's the problem? You can derive a formula for $\beta$ (as a function of $\alpha$) from the first equation, put it into the second one, solve it and get the value for $\alpha$ by substituting for $\beta$. $\endgroup$ Commented Mar 13, 2015 at 0:00
  • 1
    $\begingroup$ Presumably you intend that $X_1$ and $X_2$ are bivariate normal. It's possible for $X_1$ and $X_2$ to be normal and for them to be correlated, but for their joint distribution to be non-normal. $\endgroup$
    – Glen_b
    Commented Mar 13, 2015 at 7:20
  • $\begingroup$ I agree with @Glen_b . Lanza, please indicate whether you mean that $X_1$ and $X_2$ are bivariate normal. If the answer is no, then I should edit my answer accordingly. Thank you! $\endgroup$ Commented Mar 13, 2015 at 22:41
  • $\begingroup$ @JellicleCat Sorry, they are bivariate, I edited my post. $\endgroup$
    – Lanza
    Commented Mar 14, 2015 at 12:26
  • $\begingroup$ math.stackexchange.com/questions/446093/… $\endgroup$ Commented Mar 14, 2015 at 13:44

1 Answer 1


You say you need solve $$0=\alpha+\beta\rho\ (1)$$ $$\alpha^2 + \beta^2=1\ (2)$$

However, I think (2) is improper. You want to get two independent standard normal random variables, which are $X_1$ and $Y=\alpha X_1 + \beta X_2$. $X_1$ is made to follow standard normal. How about $Y$? $Y$ follows normal distribution, the mean of $Y$ is apparently 0, and the variance of $Y$ should be 1, so you need $1=var(Y)=\alpha^2 var(X_1)+\beta^2 var(X_2)+2\alpha\beta cov(X_1,X_2)=\alpha^2 + \beta^2 + 2\alpha\beta\rho$, which means $$1=\alpha^2 + \beta^2 + 2\alpha\beta\rho \ (3)$$ instead of (2).

Therefore, you need solve $$0=\alpha+\beta\rho\ (4)$$ $$\alpha^2 + \beta^2 + 2\alpha\beta\rho = 1\ (5)$$

From (4) you get $$\alpha=-\beta\rho\ (6)$$ after squaring you have $$\alpha^2=\beta^2\rho^2\ (7)$$ Put (6) and (7) into (5) $$\beta^2\rho^2+\beta^2-2\beta^2\rho^2=1\ (8)$$ $$\beta^2-\beta^2\rho^2=1\ (9)$$ Therefore $$\beta=\pm\sqrt\frac{1}{1-\rho^2}\ (10)$$ Using (6) and (10), you get $$\alpha=\sqrt\frac{\rho^2}{1-\rho^2},\ \beta=-\sqrt\frac{1}{1-\rho^2}$$ or $$\alpha=-\sqrt\frac{\rho^2}{1-\rho^2},\ \beta=\sqrt\frac{1}{1-\rho^2}$$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service and acknowledge you have read our privacy policy.

Not the answer you're looking for? Browse other questions tagged or ask your own question.